Unveiling the Genetic Resemblances and Phylogenetic Relationship of Species Belonging to the Family Mastacembelidae (Teleostei: Synbranchiformes) from Indian Waters - Barman, Manabjyoti; Phukan, Bipul; Talukdar, Avinash; S, Silpa (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study has been carried out to evaluate the genetic divergence among species of the family Mastacembelidae (common name: spiny eels) from India and to establish their phylogenetic relationship. Twenty reference sequences from NCBI GenBank database were obtained for five species viz. Macrognathus aral, Macrognathus aculeatus, Macrognathus guentheri, Macrognathus pancalus and Mastacembelus armatus, and used for the molecular analysis. The within species difference ranged between 0.32 to 1.12% except Mastacembelus armatus (9.00%). The lowest genetic distance was between Macrognatus guentheri and Macrognathus pancalus while the highest genetic distance was evident between Macrognathus aculeatus and Mastacembelus armatus. The findings of the present study may be used as baseline information on the molecular divergence of species belonging to the family Mastacembelidae from Indian water.